Соціально-психологічні умови й фактори формування революційної ситуації (теоретичний аспект вивчення проблеми) - Ідрісов, Бахтійор; Idrisov, Bachtior; Идрисов, Бахтиер (My University, 2019)
Вивчення питань революції та причин її формування й розвитку становить науковий інтерес у контексті зміни суспільної свідомості і її впливу на швидкість соціальних процесів. Представлено моделі та підходи, у контексті яких вивчаються причини революції. У дослід-женні застосовано підхід, що дає змогу оптимально виокремити взаємозвʼязок «причина–дія». Визначено, що зміна умов соціальної взаємодії призвела до розвитку в суспільстві негативного факторного взаємозв’язку, відображенням чого є суб’єктивні фактори, які характеризуються афективними та когнітивними діями. The study of the questions of the revolution and the reasons for its formation and development is of scientific interest in the context of changes in public consciousness and its influence on the speed of social processes. The analysis of foreign and domestic scientific works showed that the use of the concept of «cause of revolution» for different eras is ambiguous, and the explanations for the emergence and development of revolution are characterized by variability of concepts, which is caused both by differences in scientific approaches to the definition of key concepts and subjective vision by scientist’s research objectives. The article presents a classification of the most recognized foreign models and approaches in the aspect of which the causes of the revolution are studied, and accordingly, in our study, an approach is used that optimally allows you to highlight the «cause-effect» relationship. It is determined that the objective and subjective conditions for maintaining the revolutionary situation in Ukraine are changes in the system of relations in the social structure of society and the transformation of individual norms and rules to the action of a social elevator. It was emphasized that a change in the conditions of social interaction led to the development in society of an objective relationship «social disorientation – social anomie – social cynicism – social madness», characterized by a tendency to repeat and narrow in time. Their reflection is subjective factors, characterized by affective and cognitive actions of the individual in the choice of goals and methods to increase their own social status. It is emphasized that for the beginning of cardinal actions it is necessary to include the mechanism of «occasion-trigger mechanism of revolution». It is proved that the cause of Ukrainian revolutions is the socio-psychological instability of society, manifested in the interconnection of objective conditions with relative inertia and changing objective factors with each electoral cycle, and the level of interaction of subjective conditions and factors determined the intensity of development of revolution. Изучение вопросов революции и ее причин пред-ставляет научный интерес в контексте изменения общественного сознания. В исследовании применяется подход, позволяющий оптимально выделить революционную взаимосвязь «причина–действие». Определяется, что условиями сохранения революционной ситуации являются изменения в социальной структуре общества и трансформация индивидуальных норм и правил действия социального лифта. Отмечается, что смена условий социального взаимодействия привела к развитию факторной взаимосвязи, отражением которой являются аффективные и когнитивные действия.
Socio-Psychological Conditions and Factors of the Formation of a Revolutionary Situation (Theoretical Aspect of the Study of the Problem)
Keywords: зміна суспільної свідомості; трансформація соціальної й культурної систем; change in public consciousness; transformation of social and cultural systems; изменение общественного сознания; трансформация социальной и культурной систем